The Application of Learning Organization Idea at Malaysian University: A Case Study of University Malaysia Pahang (UMP) - Aini, Ahmad (Penerbit UMP, 2015)
This paper discusses the implementation of learning organization idea in one of the public universities in Malaysia, the Universiti Malaysia Pahang. The objective of this paper is to identify components that support the development and maintenance of the idea. The study analyses four understanding of learning organization based on Ortenblad (2002) that are organizational learning, learning at work, learning climate and learning structure against learning organization initiatives at the university. This paper provides some examples on the application of learning organization idea into Malaysian public university context.